(untitled) (Tanzania Medical Journal, 2007)
Objective: To study the periodontal health status of Mtwara adult population aged 40+ years. Design: A cross-sectional descriptive study Settings: Mtwara Rural district Main outcome measures: Presence of gingival bleeding on gentle probing, dental calculus, probing periodontal pocket depth (PPD): 4-5 mm or 6+ mm, according to Community Periodontal Index (CPI). Results: A total of 201 adults (males 115 (55.8%) and females 86 (44.2%)), aged 40+ years were recruited. Based on hierarchical CPI scoring (Score 0-4), no participant had healthy periodontal tissues or gingival bleeding as highest CPI score. The prevalence for calculus was 13.9% and there were more males than females that had calculus (p=0.019). The prevalence of PPD 4-5 mm and 6+ mm were 41.8% and 44.3%, respectively. The mean number of sextants with PPD 4-5 mm was higher in males than in females (p=0.009), but for PPD 6+ mm, there was no difference. Conclusion: The findings of this study population have shown an extremely high prevalence of gingival bleeding, high prevalence of calculus and periodontal disease but of low severity. The Mtwara Rural adult population aged 40+ years should be considered at increased risk for destructive periodontal disease, and hence need to plan for a preventive intervention. Keywords: Gingival bleeding, Calculus, Periodontal pockets, Community Periodontal Index, Mtwara Rural. Tanzania Medical Journal Vol. 19 (1) 2004: pp.